Pengaruh Model Pembelajaran Take and Give Terhadap Keterampilan Berdiskusi Siswa Pada pembelajaran IPAS Bab 8 Kelas IV SDN 060898 Medan T.A 2023/2024 - Christina Cahaya Mutiara Sinaga; Risma Sitohang; Laurensia M. Parangin-angin (STIKes Ibnu Sina Ajibarang, 2024)
This research aims to determine the effect of the Take and Give learning model on students' discussion skills in learning Science Chapter 8 class IV at SD Negeri 060898 Medan. The type of research used in this research is quantitative research with a Quasi Experimental approach. The subjects in this research were all fourth grade students at SD Negeri 060898 Medan. The sampling technique used was random sampling of 22 class IVA students and 22 class IVB students at SD Negeri 060898 Medan. Data analysis was carried out using quantitative analysis. From the research results, it can be concluded that there is an influence of the Take and Give learning model on students' discussion skills in learning science and science chapter 8 class IV at SD Negeri 060898 Medan. This can be seen from the posttest average of experimental class students' discussion skills which is higher than the control class, namely 37.9 > 29.7, and seen from the hypothesis test carried out by researchers based on the results of comparing t_count with t_table, namely 16.164 > 1.682 with a significant level. 5% which causes Ha to be accepted and Ho to be rejected.